Islamic Entrepreneurship Education in Vocational High Schools in Lhokseumawe - Taufiq; Siraj Siraj; Agus Muliaman; Putri Meurah Intan; Adinda Desrina (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2024)
The objective of the research on Islamic Entrepreneurship Education in Vocational High Schools in Lhokseumawe is to analyze the implementation of Islamic entrepreneurship education, focusing on the integration of Islamic values into the entrepreneurship curriculum and practices at the school. The type of research used is descriptive qualitative research. Data collection in this study used three techniques: in-depth interviews, participant observation and documentation study. The data analysis technique used is the interactive model which includes: data reduction, data presentation, and conclusion drawing. The conclusion of this study is that the implementation of the Islamic Edutechnopreneur model in Vocational High Schools can significantly contribute to improving the quality of vocational education. By integrating Islamic entrepreneurial values, schools not only produce graduates with technical skills relevant to the industrial world but also equip them with professional attitudes, independence, and entrepreneurial abilities